Flouting of Grice’s Maxims in the Humorous Utterances in American Situation Comedy 2 Broke Girls - Rafika, Rahmi; Yuliasri, Issy; Warsono, Warsono (Universitas Negeri Semarang, 2020)
In daily life, when people interact, they sometimes use humorous utterances in the conversation. Humor may occur because the speakers flout Grice’s maxims. This study aims to describe how Grice’s maxims flout in the humorous utterances in American Situation Comedy 2 Broke Girls in Season 6 Episode 3-9 and the humorous utterances usually contain laughter. The finding of this study shows that all types of maxims were flouted by the actors and there are different language styles involved in the conversations. The maxim which is flouted the most is quantity and the language style which is found the most is hyperbole. The contents of situation which cause the actors to flout Grice’s maxims are as follows; the actors flout maxim of quality when they say something which is blatantly untrue or they lacks adequate. Then, in flouting of maxim of quantity, the actors sometimes give too little information and too much information. The third, the actors flouts maxim of manner when they say ambiguous, sometime being obscure. Last, the actors flout the maxim of relation if they say something irrelevant in responding to the previous topic. This study can be concluded that Grice’s maxims flouted in humorous utterances and the language styles are also found. The most dominant maxim that flouted is quantity.